Stablecoins – Financial Instruments with Low Volatility - Dan-Cristian CEARNAU (Informatică economică, 2023)
The first distributed blockchain systems were used to power digital currencies (cryptocurrencies) such as Bitcoin, Litecoin, or Ethereum. The value of these cryptocurrencies is given by their supply and demand on the market, thus, giving rise to very high volatility. As the first cryptocurrency launched, Bitcoin (BTC) is a financial instrument recognized for its volatility. This property of Bitcoin has two implications: attracting investors who want to benefit from the increase or decrease in its value in a very short timeframe and deterring investors due to the possibility of recording substantial losses. This paper analyzes several models of digital currencies that aim to maintain a stable unit value. This unit value is expressed in a fiat currency such as the US dollar or the single European currency (euro), also called a Fiat currency. These “stable” currencies are used to allow investors in volatile instruments like Bitcoin to be able to cover their gains or losses. In addition to the usefulness of these currencies as an exchange tool in transactions with traditional digital currencies (Bitcoin, Litecoin, Ethereum, etc.), they can also be used for internet transactions without being prone to government control, as is the case with a traditional Fiat currency.